TCDMeta: a metadata model used to automatically create collections and meta-collections of the academic content in the institutional repository of the Technological Educational Institute of Crete - Tsatsakis, Nikolaos; Gougousis, Alexandros; Varvantaki, Stavroula; Tzedaki, Georgia; Panagiotakis, Mihail (Qualitative and Quantitative Methods in Libraries, 2017)
An academic institutional repository has to provide the ability of structuring its content throughout its existence, preferably according to a dynamically evolving as well as easily adaptive mechanism which categorizes all items to a multilevel structure.  The description and use of TCDMeta as a metadata model to achieve content categorization into collections and meta-collections for the institutional repository of the TEI of Crete is described in this paper. The model was built during the debugging process of the descriptive metadata for the collection of the students’ diploma theses and will give us  the ability to create collections and meta-collections other than those related to faculties, academic departments and years of creation which were used up to now.  The systematic consideration of all items provided us with a distilled knowledge of the content in our institutional repository and designated the main elements of the model: subjects’ collections related to carefully chosen keywords from a controlled vocabulary, popular topics’ collections that can help in a macroscopic study of the methods, tools, and outcomes that are related to those topics, geographic collections that contain studies and experiments held in certain geographic areas, distinguished theses collections and others.